2012
DOI: 10.1007/s00445-012-0582-4
|View full text |Cite
|
Sign up to set email alerts
|

Fumarolic pipes in the Tshirege Member of the Bandelier Tuff on the Pajarito Plateau, Jemez Mountains, New Mexico

Abstract: The objective of this study is to demonstrate the relationships among devitrification, vapor phase alteration, localization of gas emanations into fumarolic pipes, and initial deformation of the ash flow sheet during cooling and lithification. Utilizing a unique and temporary exposure of the Tshirege Member of the Bandelier Tuff near Los Alamos, New Mexico, we identify several zones of distinctly preserved fossil fumarolic activity. The fumarolic zones vary in width from a few centimeters to more than a meter.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Cristobalite is a common high‐temperature alteration mineral found in silica‐rich tuffs [ Carlos et al , 1991; Caporuscio et al , 2012] and in basalts [ Naughton et al , 1976; Hamilton et al , 2008]. Occurrences of cristobalite in similar tuffs elsewhere have been attributed to hydrothermal or vapor‐phase alteration [ Naughton et al , 1976; Keith , 1991; Stimac et al , 1996; Shimizu and Aoki , 2011; Tempel et al , 2011; Wright et al , 2011; Caporuscio et al , 2012]. Previous studies have shown that percolation of meteoric water under ambient conditions is not a likely mechanism for cristobalite formation [ Matyskiela , 1997].…”
Section: Sage Flat Hollow Sitementioning
confidence: 99%
See 2 more Smart Citations
“…Cristobalite is a common high‐temperature alteration mineral found in silica‐rich tuffs [ Carlos et al , 1991; Caporuscio et al , 2012] and in basalts [ Naughton et al , 1976; Hamilton et al , 2008]. Occurrences of cristobalite in similar tuffs elsewhere have been attributed to hydrothermal or vapor‐phase alteration [ Naughton et al , 1976; Keith , 1991; Stimac et al , 1996; Shimizu and Aoki , 2011; Tempel et al , 2011; Wright et al , 2011; Caporuscio et al , 2012]. Previous studies have shown that percolation of meteoric water under ambient conditions is not a likely mechanism for cristobalite formation [ Matyskiela , 1997].…”
Section: Sage Flat Hollow Sitementioning
confidence: 99%
“…[23] Shortly following emplacement of the Joe Lott Tuff, an open synform, the Clear Creek downwarp, developed in the region of the study area [Callaghan and Parker, 1962]. Subsequently, between $16 Ma and $14 Ma, volcanism waned and basin-fill sedimentation was prevalent.…”
Section: Geologic Settingmentioning
confidence: 99%
See 1 more Smart Citation